The Influence Of Work Stress and Work-Life Balance On Employee Job Satisfaction - Mutiara Rizky Febriani; Agung Wahyu Handaru; Sholikhah (LPPM Universitas Negeri Jakarta, 2022)
The purpose of this research are: To analyze and find out 1) The description of work stress, work-life balance, and employee job satisfaction of PT Taspen (Persero) Indonesia, 2) The influence of work stress on employee job satisfaction of PT Taspen (Persero) Indonesia, 3) The influence of work-life balance on employee job satisfaction of PT Taspen (Persero) Indonesia, 4) The research model of work stress and work-life balance in predicting employee job satisfaction of PT Taspen (Persero) Indonesia. This research was conducted on 199 employees of PT Taspen (Persero) Indonesia. Data collection techniques used interview and survey methods by distributing questionnaires which are then processed using the SPSS 21 program. This research used descriptive and causal analysis. The results of regression indicate that there is a negative and significant effect between work stress on employee job satisfaction, there is a positive and significant effect between work-life balance on employee job satisfaction.